2021
DOI: 10.1021/acsnano.1c07158
|View full text |Cite
|
Sign up to set email alerts
|

Study of Contact Electrification at Liquid-Gas Interface

Abstract: It is known that the suspended liquid droplets in clouds can generate electrostatic charges, which finally results in the lightning. However, the detailed mechanism related to the contact-electrification process on the liquid-gas (L-G) interfaces is still poorly understood. Here, by introducing an acoustic levitation method for levitating a liquid droplet, we have studied the electrification mechanism at the L-G interface. The tribo-motion between water droplets and air induced by the ultrasound wave leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 56 publications
(59 reference statements)
1
37
0
Order By: Relevance
“…Reproduced with permission. [29] Copyright 2021, American Chemical Society. liquids, such as organic solvents, inorganic solvents, ionic solutions, etc., corresponding to different solid surfaces, still requires further studies.…”
Section: Mechanism Of Liquid-interfaces-based Contact Electrificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Reproduced with permission. [29] Copyright 2021, American Chemical Society. liquids, such as organic solvents, inorganic solvents, ionic solutions, etc., corresponding to different solid surfaces, still requires further studies.…”
Section: Mechanism Of Liquid-interfaces-based Contact Electrificationmentioning
confidence: 99%
“…Usually, a higher droplet height results in the full triboelectrification between liquid and air, and the density of the surface charge of the droplet increases until saturation. [29,63] Additionally, as the height increases, the droplet speed and impact force increase. [60,68] As shown in Figure 10b-iii,c-iii, there is an increasing tendency of LI-TENG's output as the height of the droplet increases.…”
Section: Dropletmentioning
confidence: 99%
See 2 more Smart Citations
“…Most stretchable TENGs utilize polymer materials, such as all kinds of elastomers. Meanwhile, many studies have revealed that the characteristics and the density of functional groups in a polymer can determine the electron transfer process during contact electrification. For the commonly used stretchable triboelectric materials, the applied strain can induce many changes in the electrification process, while the underlying mechanism remains ambiguous. Usually, a change in the effective contact area , and the induced intermolecular forces , is considered to be the major effect changing the electrification performance.…”
mentioning
confidence: 99%